A critical role for the TAR element in promoting efficient human immunodeficiency virus type 1 reverse transcription. - Harrich, D (1996)
The regulation of human immunodeficiency virus type 1 (HIV-1) gene expression is dependent on the transactivator protein Tat and an RNA element extending from the transcription initiation site to +57 known as TAR. TAR forms a stable RNA secondary structure which is critical for high levels of HIV-1 gene expression and efficient viral replication. Using a genetic approach, we isolated HIV-1 mutants in TAR that were competent for high levels of gene expression but yet were markedly defective for viral replication. Single-cycle infections with these viruses demonstrated that they were defective in the initiation of reverse transcription. Additional mutational analysis revealed a variety of other HIV-1 TAR mutants with the same defective phenotype. Thus, in addition to the well-characterized role of the primer binding site, other RNA elements within the HIV-1 genome are also critical in the regulation of reverse transcription. These studies demonstrate that HIV-1 TAR RNA is a key regulator of the reverse transcription and illustrate how a unique RNA structure can modulate diverse regulatory processes in the HIV-1 life cycle crucial for efficient viral replication.